Chlorine Release From Common Chlorides by Martian Dust Activity. Issue 6 (11th June 2020) - Wang, Alian; Yan, Yuanchao; Jolliff, Bradley L.; McLennan, Scott M.; Wang, Kun; Shi, Erbin; Farrell, William M.
Abstract: Chlorine is one of the highly mobile elements that participated in early aqueous chemistry and later alteration in Mars history. Our new experimental results suggest that chlorine could cycle on present‐day Mars between the atmosphere and surface, driven by multiphase redox plasma chemistry induced by current Martian dust activity (dust storms, dust devils, and grain saltation). We present two sets of experimental results that demonstrate the instantaneous release of chlorine from seven common chlorides during a medium strength electrostatic discharge (ESD) process that induced plasma chemistry in a Mars environmental chamber. Results include (1) the direct detection of a plasma emission line at 837.8 nm of the first excited state of the Cl atom ( Cl‐I ) by in situ plasma spectroscopy during the ESD process for MgCl2, FeCl2, and AlCl3 and (2) the characterization of Cl‐bearing phases in the films deposited on the upper electrode after 7 hr of ESD exposure on each of seven chlorides (NaCl, KCl, CaCl2, MgCl2, FeCl2, AlCl3, and FeCl3 ), using Raman spectroscopy, X‐ray diffraction (XRD), scanning electron microscopy (SEM), energy‐dispersive X‐ray (EDX) spectroscopy, and X‐ray photoelectron spectroscopy (XPS). This study is part of a series of laboratory investigations on the Martian atmosphere and surface interaction induced by electrochemistry. Plain Language Summary: Chlorine has a broad distribution on the surface of Mars. Compared to Martian meteorites, high concentrations of Cl was found in all Martian surface materials analyzed during landed missions on Mars. A "Cl cycle" has been driven by volcanic activity and aqueous chemistry throughout Martian history. A Cl cycle still exists on present‐day Mars, and in this work, we seek to determine a mechanism that may drive the exchange of chlorine between the surface and the atmosphere. We present two sets of experimentally observed evidences for the instantaneous chlorine release from common chlorides during the process of electrostatic discharge (ESD), that suggest the electrochemistry induced by Martian dust activity may be an important process to drive the Cl cycle between the surface and atmosphere on present‐day Mars. The highly reactive species, such as the Cl at excited state, oxychlorates, and gaseous free radicals, generated by ESD process on Mars are of great importance. The influences of electrochemistry induced by Martian dust events on the habitability and on the search for the trace of life at the surface and in shallow subsurface will need further investigation. Key Points: A plasma line of Cl at 1st excited state was observed during the electrostatic discharge (ESD) process on chlorides in a Mars chamber Cl‐bearing film deposits were found on the upper electrode after 7 hours of ESD processes on each of the seven common chlorides The ESD process induced by dust activity on present day of Mars can drive the chlorine cycling between surface and atmosphere